Innovative liposomal coumarin: A promising solution for enhancing soft white cheese quality - Salameh Alqaraleh; Laila Al-Omari; Ghadeer Mehyar; Moath Alqaraleh; Walhan Alshaer; Hiba Abdelnabi; Sarah Jaradat (PLoS ONE, 2025)
Background Coumarin is a natural bioactive compound found in many plants and acquires antibacterial, antioxidant and anticoagulant activities. The antibacterial activity of coumarin has never been tested after being encapsulated in liposomes. This study was carried out to screen the main functional components of Rubus canescens DC crude extract (CE), develop a coumarin nanoliposome, and test its anti-bacterial and antioxidant properties. Methods R. canescens DC CE was screened for its main functional compounds using liquid chromatography-mass spectrometry (LC-MS). Pure commercial coumarin was loaded into liposomes and characterized in terms of surface morphology, hydrodynamic diameter, zeta potential, and encapsulation efficiency (EE). The antioxidant activity of coumarin was evaluated against ascorbic acid. The antibacterial activity of both coumarin alone and liposome-encapsulated coumarin against Staphylococcus aureus, Salmonella typhimurium, and Pseudomonas aeruginosa inoculated in soft white cheese (SWC) was also evaluated. Results The predominant natural constituent of R. canescens DC CE, was coumarin. Comparing the DPPH scavenging activity of coumarin to that of ascorbic acid, coumarin exhibited an insignificant effect (p ≥ 0.05). The minimum inhibitory concentration (MIC) values for coumarin against P. aeruginosa, E. coli, Staph. aureus, S. typhimurium, and L. monocytogenes were 2.5, 2.5, 2.5, 1.25, and 1.25 µg/ml, respectively. The minimum bactericidal concentration (MBC) values for coumarin against these microorganisms were 5, 5, 5, 2.5, and 2.5 µg/ml, respectively. Coumarin was successfully loaded into nanoliposomes, which had a polydispersity index (PDI) of 0.36 ±  0.35 Đ, hydrodynamic diameter of 127.8 ±  0.3 nm, zeta-potential of -61.03 ±  2.9 mV, and EE of 40.93 ±  0.2%. Both the coumarin alone and the liposome loaded with coumarin showed antibacterial effects against the inoculated bacterial strains in SWC over a 30-day storage period at 4°C. Conclusions Coumarin was successfully formulated into a nanoliposome, and showed antibacterial activity against P. aeruginosa, S. aureus, and S. typhimurium.